Effectiveness of Blended Learning in Teaching Writing of EFL Students - Aulia, Nur; Zia Ul Haq, Muhammad; Junaid (FKIP Unismuh Makassar, 2023)
The objective of this research is to find out whether or not the use of blended learning model effective in improving students writing competence at ten grade of SMK Muhammadiyah 2 Bontoala Makassar.This study applied a pre-experimental design using a quantitative approach. The population of this study was the tenth grade at SMK Muhammadiyah 2 Bontoala Makassar which consisted of 128 students. Then, the sample from this study, namely class X TSM was taken using a purposive sampling technique which consisted of 30 students.The findings of this study indicated that class X TSM at SMK Muhammadiyah 2 Bontoala Makassar has a sufficient score in the pre-test. After treatment, students' writing competence in writing recount text in terms of grammar and mechanics increased significantly. It was proved by the t-test value in terms of grammar is 17.385, it is higher than 2.045. And also, it was proved by the t-test value in terms of mechanics 31.007, it is higher than the t-table value 2.045. This indicated that H1 (alternative hypothesis) was accepted and H0 (null hypothesis) was rejected. It means that there was a significant difference of the students' writing competence before and after using the blended learning model.